Philosophy, Science, Education and Culture - Nola, Robert. author. aut Link
XIV, 490 p.
Keywords: Currents such as epistemological and social constructivism, postmodernism, and certain forms of multiculturalism that had become fashionable within science education circles in the last decades lost sight of critical inquiry as the core aim of education. In this book we develop an account of education that places critical inquiry at the core of education in general and science education in particular. Since science constitutes the paradigm example of critical inquiry, we explain the nature of science, paying particular attention to scientific methodology and scientific modeling and at the same time showing their relevance in the science classroom. We defend a universalist, rationalist, and objectivist account of science against epistemological and social constructivist views, postmodernist approaches and epistemic multiculturalist accounts.